Learning Grammar Autonomously through Metacognitive Strategies: An Experiment (Journal of NELTA, 2011)
Knowing how to learn a language maximizes the chances of effective learning. Metacognition, an emerging concept in cognitive psychology, aids learners to enrich their knowledge of the learning process and makes them autonomous learners. This paper details an experiment conducted with fifty freshmen in college on autonomous learning of 'concord' using metacognitive strategies. This experiment is an attempt to verify whether students can learn English grammar autonomously when they are trained to use metacognitive knowledge and strategies. This experiment uses the method described by Best and Kahn (2000).Key words: Metcognitive knowledge; Met cognitive strategies; Learner autonomyJournal of NELTAVol. 15 No. 1-2 December 2010Page: 146-150Uploaded date: 4 May, 2011DOI: 10.3126/nelta.v15i1-2.4620